2021
DOI: 10.1007/s11043-021-09486-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of soft polymeric materials using a fractal viscoelastic model

Abstract: Soft materials are known for their plethora of biomedical applications, intricate structure-property correlation and nonlinear mechanical response. Multiple length-time scale phenomena and hierarchical structure results in their nonlinearity. Phenomenological and continuum mechanical models have been developed to predict their mechanics, which have mostly been very material-specific with inability to predict the mechanics of different types of soft materials simultaneously. This shortcoming has been addressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Despite its accuracy, its use is limited due to the large number of constants required to mathematically define the model. Several models using springs and dashpots have been developed for large deformations, chain networks, damage accumulation, cyclic loadings, and strain-softening conditions [168,169]. It has been shown that a combination of linear and nonlinear springs with a nonlinear dashpot can appropriately consider the effects of strain rate and relaxation [168].…”
Section: Viscoelasticity and Viscoplasticitymentioning
confidence: 99%
“…Despite its accuracy, its use is limited due to the large number of constants required to mathematically define the model. Several models using springs and dashpots have been developed for large deformations, chain networks, damage accumulation, cyclic loadings, and strain-softening conditions [168,169]. It has been shown that a combination of linear and nonlinear springs with a nonlinear dashpot can appropriately consider the effects of strain rate and relaxation [168].…”
Section: Viscoelasticity and Viscoplasticitymentioning
confidence: 99%
“…However, they cannot accurately characterize the material nonlinearity and time-dependent behaviors that is often seen in biomedical materials. Therefore, in this section, inspired by [44], the classical Maxwell model is modified as the nonlinear fractal order Maxwell model to characterize the nonlinear and timedependent behaviors caused by the interaction of MR fluid and the PU sponge. This model includes two parts: normal force model and shear force model.…”
Section: Modeling Of the Tactile Display Devicementioning
confidence: 99%
“…At present, it is worth noting the relevant research on the adhesion of soft matters. From the perspective of adhesion mechanics, researchers have carried out in-depth exploration of the behavior characteristics, theoretical analysis and test methods of soft matters, and have achieved fruitful results in the fields of biomechanics, interface and contact mechanics and colloid mechanics . However, the research on the adhesion of soft matter surfaces is still weak, and the combination of theory and experiment is more urgent.…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of adhesion mechanics, researchers have carried out in-depth exploration of the behavior characteristics, theoretical analysis and test methods of soft matters, and have achieved fruitful results in the fields of biomechanics, 4 interface and contact mechanics 5 and colloid mechanics. 6 However, the research on the adhesion of soft matter surfaces is still weak, and the combination of theory and experiment is more urgent. In addition, current instrument is commonly photographed from the bottom 7 or side 8 of indentation, which requests the research object must be a thinner transparent soft matter to obtain the adhesion deformation of the contact surface.…”
Section: ■ Introductionmentioning
confidence: 99%